2014
DOI: 10.1007/s10591-014-9316-4
|View full text |Cite
|
Sign up to set email alerts
|

Reintegration Stress and Family Mental Health: Implications for Therapists Working with Reintegrating Military Families

Abstract: Military families respond and adjust differently to reintegration stressors with some families coping well with these changes while other families do not. It is important to understand factors that contribute to reintegration stress since reintegration stress can affect their own and their family's emotional health and well-being for months if not years into the future. This study addresses the factors that contribute to more positive outcomes and reduced reintegration stress, for reintegrating military famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…Other studies with military spouses revealed feelings of lack of support during missions, specifically, the absence of military services with which they felt they could not count on (Carreiras, 2015;Martins et al, 2014), lack of awareness of their existence (Manigart et al, 2015), or even be considered as secondary resources (Martins et al, 2014). However, and in order for the military to feel good during the mission, military services will have to support their family by enhancing "communication" between the military and his family members (Gottman, Gottman, & Atkins, 2011) and provide necessary support resources (Marek & D'Aniello, 2014). Despite these concerns, studies with Portuguese military families further highlight the impact of missions on marital and parental contexts (Barbudo et al, 2014;Bóia et al, 2018;Martins et al, 2014), neglecting the extended family relationships and the communication between the deployed military and other elements of the family system, such as parents and siblings.…”
Section: Rutina Comunicación Y Afectos De Los Hermanos Y Padres De Lmentioning
confidence: 99%
“…Other studies with military spouses revealed feelings of lack of support during missions, specifically, the absence of military services with which they felt they could not count on (Carreiras, 2015;Martins et al, 2014), lack of awareness of their existence (Manigart et al, 2015), or even be considered as secondary resources (Martins et al, 2014). However, and in order for the military to feel good during the mission, military services will have to support their family by enhancing "communication" between the military and his family members (Gottman, Gottman, & Atkins, 2011) and provide necessary support resources (Marek & D'Aniello, 2014). Despite these concerns, studies with Portuguese military families further highlight the impact of missions on marital and parental contexts (Barbudo et al, 2014;Bóia et al, 2018;Martins et al, 2014), neglecting the extended family relationships and the communication between the deployed military and other elements of the family system, such as parents and siblings.…”
Section: Rutina Comunicación Y Afectos De Los Hermanos Y Padres De Lmentioning
confidence: 99%
“…Tendo em conta o que foi referido previamente, é necessário juntar esforços para apoiar estas crianças/jovens e as suas famílias, sensibilizando a comunidade escolar e os serviços primários de saúde para as necessidades desta população, providenciando as ferramentas necessárias ao trabalho com estas famílias (Marek & D'Aniello, 2014). Estas entidades podem ser importantes aquando das missões internacionais, pois as crianças estão possivelmente mais vulneráveis (Acion, Ramirez, Jorge, & Arndt, 2013).…”
Section: Programas De Apoio àS Famílias Militaresunclassified
“…Many service members report separation from family members during deployments as their biggest noncombatrelated stressor (Marek and D'Aniello 2014). These absences create a number of difficulties for all members of the family, starting with the parental dyad, both of whom are heavily stressed from pre-deployment through the often problematic process of adaptation to their post-deployment reunification (Baptist et al 2011).…”
Section: Adverse Outcomes For Children Of Military Familiesmentioning
confidence: 99%
“…In addition to the vicarious effects of stressors and even mental health problems affecting their parents, military-connected children are presented with a wide range of challenges to their own adjustment, including the length, frequency, and number of deployments, shifts in roles and routines that accompany the reintegration of returning service members, and constant concern about the possibility of redeployment. Although higher levels of adjustment by the at-home parent and the minimization of disruption to familiar activities are often the best predictors of a child's ability to adjust to separations and losses, these protective factors are far outweighed by the numerous risk factors military children face (Hollingsworth 2011;Huebner et al 2009;Marek and D'Aniello 2014). For many of these children, parental deployment is associated with depression, anxiety, and isolation (Lester et al 2010).…”
Section: Adverse Outcomes For Children Of Military Familiesmentioning
confidence: 99%